2017
DOI: 10.20944/preprints201712.0185.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early Detection and Diagnosis of Neonatal Intrahepatic Cholestasis Caused by Citrin Deficiency Missed by Newborn Screening Using Tandem Mass Spectrometry

Abstract: Abstract:Citrullinemia is the earliest identifiable biochemical abnormality in 13neonates with intrahepatic cholestasis due to a citrin deficiency (NICCD) and it has 14 been included in newborn screening panels using tandem mass spectrometry. 15However, only one neonate was positive among 600,000 infants born in Sapporo 16 city and Hokkaido, Japan between 2006 and 2017. We investigated 12 neonates with 17 NICCD who were initially considered normal in newborn mass screening (NBS) by 18 tandem mass spectrometry,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Of the total 222 patients enrolled in this study, 59 patients with citrin deficiency had already been published before: 1 patient in, 22 8 patients in, 23 and 52 patients in 24 ; two patients were part of two independent publications 23,24 …”
Section: Methodsmentioning
confidence: 99%
“…Of the total 222 patients enrolled in this study, 59 patients with citrin deficiency had already been published before: 1 patient in, 22 8 patients in, 23 and 52 patients in 24 ; two patients were part of two independent publications 23,24 …”
Section: Methodsmentioning
confidence: 99%
“…However, a study in Texas in which 10 patients received genetic testing found evidence for Arabic, Pakistani, French Canadian, and Northern European family origin . NBS with tandem mass spectrometry now takes place in Japan and Taiwan …”
Section: Resultsmentioning
confidence: 99%
“…88 NBS with tandem mass spectrometry now takes place in Japan and Taiwan. 89,90 In the neonatal period, the buildup of bile caused by NICCD is associated with failure to thrive and dyslipidemia. 86 Early signs may involve a "chubby face," which resolves after 1 year.…”
Section: Urea Cycle Mitochondrial Transporter Defects 331 | Citrin Deficiencymentioning
confidence: 99%
“…Of the five patients eventually diagnosed with CITRIN deficiency, only one had significantly elevated citrulline on NBS and none had elevated orotic acid. It has previously been shown that most newborns with CITRIN deficiency have citrulline levels below the cutoff 33 . Furthermore, it is not surprising that including orotic acid determination in the screen did not contribute to the diagnosis of CITRIN deficiency.…”
Section: Discussionmentioning
confidence: 99%